2023
DOI: 10.3389/fneur.2023.1050369
|View full text |Cite
|
Sign up to set email alerts
|

Utility of low-profile visualized intraluminal support (LVIS™) stent for treatment of acutely ruptured bifurcation aneurysms: A single-center study

Abstract: ObjectiveStent-assisted coiling has been increasingly used in the treatment of intracranial aneurysms. However, its application in ruptured bifurcation aneurysms remains controversial and challenging. This study aimed to present the safety and feasibility of low-profile visualized intraluminal support (LVIS™, LVIS, and LVIS Jr.) stent for acutely ruptured bifurcation aneurysms.MethodsA total of 41 patients with acutely ruptured intracranial aneurysms arising at the bifurcation were treated with LVIS™ stent-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, due to the lack of large-scale or prospective studies, it is still challenging to justify the use of stent-assisted coiling in the treatment of ruptured cerebral aneurysms. 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of large-scale or prospective studies, it is still challenging to justify the use of stent-assisted coiling in the treatment of ruptured cerebral aneurysms. 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…15) In another report on SAC with LVIS for ruptured bifurcation aneurysms,theratesofcompleteocclusionduringthefollow-up period,intraproceduralthrombosis,andintraoperativehem-orrhagewere83.3%,4.9%,and2.4%,respectively. 16) InthemostrecentreportonSACtreatmentforWNBAs, theratesofcompleteocclusionduringfollow-upandprocedure-related permanent morbidity were 80.8%-90.9% and1.5%-8.6%,respectively. [17][18][19] Althoughthesestudies have shown favorable results, treatment of WNBAs in which both branches are involved in the neck can be very difficultusingasinglestent.Insuchcases,developmental techniques such as the waffle cone technique orY-stentassistedcoilingmaybeapplied.Neck-bridgingstentsfor coil embolization not only provide a mechanical scaffolding effect but also lead to the development of flow-diverterstents,focusingontheflow-divertinghemodynamiceffect.…”
Section: Stent-assisted Coilingmentioning
confidence: 99%
“… 15) In another report on SAC with LVIS for ruptured bifurcation aneurysms, the rates of complete occlusion during the follow-up period, intraprocedural thrombosis, and intraoperative hemorrhage were 83.3%, 4.9%, and 2.4%, respectively. 16) …”
Section: Stent-assisted Coilingmentioning
confidence: 99%
“…In light of recent advancements in technology and material sciences, endovascular intervention techniques have emerged as significant therapeutic modalities for managing intracranial aneurysms ( 1 ). These techniques have garnered preference from both patients and clinicians owing to their minimally invasive nature and expedited recovery period ( 2 , 3 ). Nonetheless, the execution of endovascular embolization therapy, whether it employs simple coil embolization or is supplemented by stents or balloons, faces a principal technical challenge in accurately navigating the microcatheter into the aneurysm sac and ensuring its stability therein ( 4 ).…”
Section: Introductionmentioning
confidence: 99%